Reproduction De Heterotis Niloticus (Cuvier, 1829) De La Riviere Agneby (Cote d’Ivoire) - Kessia Irène, Kouakou Fokouo; Tiéhoua, Koné; Yaya, Soro; Konan, N’Da; Mamadou, Ouattara (European Scientific Journal, ESJ, 2016)
The reproductive biology of Heterotis niloticus has been studied from monthly samples taken from artisanal fishing on the Agneby river during the period june 2013 to May 2015. The whole sample consisted of 498 specimens of which 269 females and 229 males were examined. Sex-ratio observed was in favour of females (1: 1.17; X2 = 3.21; p > 0.05). The monthly evolution of the gonado-somatic index (GSI), the liver-somatic index (LSI), the condition factor (K) and maturation stages suggests that this fish has two periods of reproduction. The two periods were respectively from june to august and from november to december. The standard length at first sexual maturity was 490.6 mm for females and 436.3 mm for males. The absolute fecundity was ranged from 5424 to 25591 oocytes in females of 595 mm to 780 mm standard length. The relative fecundity was 3752± 1491 oocytes/kg of female.